Essential Oils from Monarda fistulosa: Chemical Composition and Activation of Transient Receptor Potential A1 (TRPA1) Channels - Ghosh, Monica (Molecules, 2020)
Little is known about the pharmacological activity of Monarda fistulosa L. essential oils. To address this issue, we isolated essential oils from the flowers and leaves of M. fistulosa and analyzed their chemical composition. We also analyzed the pharmacological effects of M. fistulosa essential oils on transient receptor potential (TRP) channel activity, as these channels are known targets of various essential oil constituents. Flower (MEO(Fl)) and leaf (MEO(Lv)) essential oils were comprised mainly of monoterpenes (43.1% and 21.1%) and oxygenated monoterpenes (54.8% and 77.7%), respectively, with a high abundance of monoterpene hydrocarbons, including p-cymene, γ-terpinene, α-terpinene, and α-thujene. Major oxygenated monoterpenes of MEO(Fl) and MEO(Lv) included carvacrol and thymol. Both MEO(Fl) and MEO(Lv) stimulated a transient increase in intracellular free Ca(2+) concentration ([Ca(2+)](i)) in TRPA1 but not in TRPV1 or TRPV4-transfected cells, with MEO(Lv) being much more effective than MEO(Fl). Furthermore, the pure monoterpenes carvacrol, thymol, and β-myrcene activated TRPA1 but not the TRPV1 or TRPV4 channels, suggesting that these compounds represented the TRPA1-activating components of M. fistulosa essential oils. The transient increase in [Ca(2+)](i) induced by MEO(Fl)/MEO(Lv), carvacrol, β-myrcene, and thymol in TRPA1-transfected cells was blocked by a selective TRPA1 antagonist, HC-030031. Although carvacrol and thymol have been reported previously to activate the TRPA1 channels, this is the first report to show that β-myrcene is also a TRPA1 channel agonist. Finally, molecular modeling studies showed a substantial similarity between the docking poses of carvacrol, thymol, and β-myrcene in the binding site of human TRPA1. Thus, our results provide a cellular and molecular basis to explain at least part of the therapeutic properties of these essential oils, laying the foundation for prospective pharmacological studies involving TRP ion channels.